STUDENTS’ PERCEPTIONS ON THE USE OF ENGLISH SONGS IN LISTENING CLASSES IN GRADE XI OF SMAN 11 - Nurrahmah Salsabila; Suyadi Suyadi; Nurul Fitri (JELT: Journal of English Language Teaching, 2026)
This research aims to explore the perceptions of eleventh-grade students at SMAN 11 Jambi City regarding the use of English pop songs, particularly "Fight Song" by Rachel Platten, as a learning medium in listening classes. This qualitative study involved 36 students from class XI F7 as participants, selected through purposive sampling. Data were collected through questionnaires and unstructured interviews. The questionnaire consisted of 17 Likert-scale statements focused on students’ perceptions of English songs in learning listening, while the interviews provided deeper insight into student experiences and thoughts. The findings showed that most students had positive perceptions of using English songs in listening activities. They reported increased motivation (85%), improved focus and relaxed learning atmosphere (76– 77%), enhanced listening skills and pronunciation (73–77%), and found songs to be efficient and enjoyable learning media. However, memorizing new vocabulary through songs was perceived as more difficult (67%) due to fast tempo, idiomatic expressions, and unfamiliar words. In conclusion, English pop songs especially those with relatable themes and easy-to-follow lyrics can be a valuable tool in enhancing students’ motivation and listening skills. This study supports the integration of music-based learning strategies in EFL classrooms to create engaging, effective, and student-centered learning experiences.